The Influence of Perceived Ease of Use and Perceived Usefulness on the Intention to Use QRIS as a Digital Payment Solution among Generation Z in Ternate City - Nazwa Nurfadia; Fitria Hi Mhd Amin; Sudin Yamani (Journal Social Society, 2026)
The urgency of this research lies in understanding the factors that influence Generation Z's intention to adopt QRIS as a digital payment solution, thereby supporting the acceleration of financial digitalization and the development of a cashless society in Ternate City. This study examines the influence of perceived ease of use and perceived usefulness on the intention to use QRIS (Quick Response Code Indonesian Standard) among Generation Z in Ternate City. The study employs a quantitative approach with an associative research design based on the Technology Acceptance Model (TAM). The research was conducted in Ternate City, Indonesia, involving Generation Z users as the research subjects. A purposive sampling technique was applied to select 50 respondents who were familiar with digital payment systems and QRIS services. Data were collected through structured questionnaires distributed directly to respondents. The collected data were analyzed using multiple linear regression analysis to determine the relationship between perceived ease of use, perceived usefulness, and behavioral intention. To ensure data quality, validity and reliability tests were conducted before hypothesis testing. The findings reveal that perceived ease of use and perceived usefulness simultaneously have a significant effect on behavioral intention to use QRIS, with a coefficient of determination (R²) of 50.4%. Partially, perceived usefulness has a statistically significant effect on behavioral intention, while perceived ease of use is not significant at the 5% significance level but becomes marginally significant at the 10% level. These results indicate that perceived usefulness plays a more dominant role in encouraging Generation Z to adopt QRIS as a digital payment method. The study suggests that stakeholders should strengthen educational and promotional strategies emphasizing the practical benefits and efficiency of QRIS to increase user adoption among young consumers.